ANALISIS MEKANISME PENYELESAIAN SENGKETA MEDIS ANTARA PASIEN DAN TENAGA KESEHATAN: PERBANDINGAN JALUR PROFESI DAN JALUR PENGADILAN - Gunawan Widjaja; Andreas Harry (Jurnal Kesehatan, 2025)
This study aims to analyse the mechanism of medical dispute resolution between patients and health professionals in Indonesia by comparing professional and judicial channels through a normative legal literature review approach. The analysis reveals that the professional route, such as through the Indonesian Medical Disciplinary Honour Council (MKDKI) and other non-litigious resolution mechanisms, is more consultative, faster, administrative in nature, and maintains confidentiality for all parties, but remains limited in terms of compensation for patients. Conversely, the court system offers litigation mechanisms with final and binding decisions and the potential for compensation for patients, but carries risks of high costs, lengthy processes, and psychological impacts on both patients and healthcare workers. Both contribute to protecting the rights of patients and healthcare workers, but further regulatory strengthening and synergy between the two mechanisms are needed to achieve more fair, effective, and restorative justice-oriented resolution of medical disputes in Indonesia.